National health and budget impact of implementing the WHO HEARTS hypertension control program in Bangladesh - Anirudh Pidugu; Sarah Pickersgill; David Watkins; Jami Husain; Deliana Kostova; Margaret Farrell; Mohammad Haider; Shamim Jubayer; Renesa Tarannum; Mahfuzur Bhuiyan; Andrew E. Moran, MD; Sohel Choudhury, PhD (Elsevier, 2022)
Background: About a fifth of adults in Bangladesh have hypertension; only 13% of Bangladesh adults living with hypertension have their blood pressure controlled (<140/90 mmHg). To address the growing burden of hypertension in low-income and middle-income countries, the WHO recommends implementing the HEARTS technical package. HEARTS outlines a practical approach to cardiovascular disease (CVD) prevention in primary care settings, including risk factor screening, diagnosis, treatment, and patient counseling. The Bangladesh Ministry of Health and Family Welfare and the National Heart Foundation of Bangladesh implemented the HEARTS programme in four district health complexes in Sylhet Division starting in 2019. To inform Bangladesh's health care policies, we translated Bangladesh HEARTS programme effectiveness and cost estimates into projections of national health and budget impact for nationwide programme scale-up. Methods: We used an interactive, web-based model to project CVD deaths averted based on observed facility-based hypertension control rates and used local costs to obtain budget impact estimates of national HEARTS programme implementation. We also explored three alternative scenarios: reducing medication costs by 50%, increasing team-based care with larger roles for nurses and community health workers, and removing laboratory costs. Relative improvement in hypertension control observed in the HEARTS programme (from 26% to 46% in the four districts over 24 months) was applied to the 13% baseline national control rate resulting in a projected improvement to 33% at national scale. The costs of the hypertension programme were quantified with a standard HEARTS costing tool that was deployed in the four district health complexes. The costing tool recorded and calculated unit costs for hypertension screening, CVD risk assessment, health-care worker time or compensation, and drug prices. Findings: An absolute improvement of 20 percentage points in the national hypertension control rate, from 13% to 33%, would save 9400 lives. Extrapolating local programme costs to the national level resulted in a budget of US$599 million by 2030. Reducing medication costs would lower the budget impact by 42·6%. Increasing team-based care would not substantively affect the cost. Removing laboratory costs would lower the budget by 14%. Combining these innovations would lower the projected cost by 56·9%. Interpretation: Implementing the HEARTS programme in Bangladesh might improve hypertension control and save 9400 lives at a budget impact of $599 million by 2030. Increased task sharing and lower medication prices have potential to reduce costs and make reaching hypertension control goals more affordable and sustainable for Bangladesh. Funding: Columbia University Global & Population Health Summer Research Fellowship.